Data Forgery in Indonesian E-Commerce: Harmonizing Sharia Principles and Positive Law for Consumer Protection - Ika Atikah; Hadiat Hadiat; Dian Febriyani (UIN Siber Syekh Nurjati Cirebon, 2025)
This article aims to analyze how the harmonization between Sharia principles and positive law can strengthen consumer protection against data forgery in Indonesian e-commerce transactions. The background of this study lies in the growing risks of identity manipulation, fictitious transactions, and consumer rights violations in the era of digital trade. Normatively, Sharia emphasizes honesty (sidq) and trustworthiness (amanah) as the foundation of contractual relations, while Indonesia’s positive law provides a formal framework through the ITE Law, the Consumer Protection Law, and the Personal Data Protection Law. The research applies a normative juridical method by examining legislation, fatwas, and relevant literature. The findings show that although positive law offers legal instruments, its enforcement remains weak; meanwhile, Sharia economic law underscores ethical compliance as the basis of protection. The academic contribution of this study is to offer a conceptual framework that integrates Sharia ethics with positive legal regulations to reinforce legal certainty, build consumer trust, and promote the sustainability of Indonesia’s digital economic growth.Keywords: Data Forgery; E-commerce; Consumer Protection; Sharia Economic Law; Positive Law